The prevalence of sleep impairments and predictors of sleep quality among patients with asthma. (3rd April 2021) - Braido, F.; Baiardini, I.; Ferrando, M.; Scichilone, N.; Santus, P.; Petrone, A.; Di Marco, F.; Corsico, A. G.; Zanforlin, A.; Milanese, M.; Steinhilber, G.; Bonavia, M.; et al.
Abstract: Background: Sleep is a significant dimension of daily life. However, only a few studies have examined the sleep quality of asthmatics in a real-world clinical settings. Objective: This study is aimed to estimate the prevalence of sleep impairments among asthmatic patients and examine the relationship between sleep quality, asthma control, rhinitis symptoms, and sociodemographic characteristics. Methods: The present study adopted the observational cross-sectional research design that has been designed by the Italian Respiratory Society and used valid assessments to measure the study variables. Results: Data from 1150 asthmatic patients (mean age 51.01 years ± 16.03) were subjected to analysis. 58.3% of the patients had impaired sleep quality (Pittsburgh Sleep Quality Index [PSQI] total scores > 5), and their mean PSQI score was 5.68 (SD = 3.4). A significant correlation emerged between sleep quality and asthma control ( p  = 0.0001) and a significant albeit weak correlation emerged between PSQI total scores and Total 5 Symptoms Score ( r  = 0.24, p  = 0.0001). Sleep quality was significantly associated health-related quality of life [HRQoL]. ( r  = 0.50, p  < 0.001). After exclusion of patients at risk for Obstructive Sleep Apnea Syndrome (OSAS) and Gastro Esophageal Reflux Disease (GERD), the most important determinants of PSQI score were HRQoL, In the entire sample asthma control is the strongest predictor of both sleep quality and HRQoL. Conclusions: The results of this real-world study highlight the prevalence, impact and predictors of sleep disturbances in asthmatic patients and suggest the need for physicians to detect poor sleep quality